Synthesis of Nano Porous Carbon derived from Vinasses Wastes for Crystal Violet Adsorption Application - Phetcharat Nenyoo; Anuchit Jaruvanawat; Atthapon Srifa; Worapon Kiatkittipong; Apiluck Eiad‐ua; Suttichai Assabumrungrat (IOP Conference Series Materials Science and Engineering, 2023)
Abstract An approach to removing crystal violet (CV) dye from aqueous solutions was investigated by nano porous carbon (NC) derived from vinasse waste. The NC was prepared via pyrolysis carbonization and potassium hydroxide chemical activation process. The NC was characterized by TGA, FTIR, and BET analysis. The optimal condition of the NC was used to adsorb CV dye in aqueous solutions at room temperature. Different initial CV concentrations and contact times were investigated to find the effect of these parameters. The NC was found efficient and can be used as a feasible alternative for removing CV dye from aqueous solutions. The NC was synthesized at activation temperature of 900 °C and the 1:1 precursor - activator (KOH) ratio provided the pore size of 3.285 nm and the maximum surface area 1,018 m 2 /g, which was an optimal condition for the crystal violet adsorption. Crystal violet was highly adsorbed within 5 minutes and then was equilibrium within 30 minutes of the contact time. The amount of dye ion adsorbed onto adsorbent was 3.3, 7.2, 11.2, and 19.1 mg/g, respectively.
Keywords: Adsorption and biosorption for pollutant removal; Mesoporous Materials and Catalysis; Supercapacitor Materials and Fabrication